A sunless sea [compact disc, unabridged] - Perry, Anne (Perry, Anne. William Monk novel, 2012)
A high-end prostitute is found brutally murdered on the London docks, and Monk's quest to discover the truth behind her death leads him down a shocking path, littered with secrets that have been buried since the infamous Opium Wars. Monk must unravel the victim's link to the widow of a dead doctor, and the doctor's vanished report on the misuse of opium, before the killer strikes again.